Hubungan yang Mempengaruhi Kepuasan Pelanggan dalam Layanan E-commerce: Menuju Hubungan yang Berkelanjutan - Duma Sari Sirait; Dwi Novi Wulansari (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The development of digital technology has driven a significant increase in the use of e-commerce services in Indonesia, which has an impact on changes in people's consumption behavior. This study aims to analyze the relationship between factors that influence customer satisfaction in e-commerce services towards sustainable relationships. The research method used is quantitative with a survey approach to 100 respondents who use e-commerce in Indonesia, and data analysis using multiple linear regression. The results of the study indicate that all instruments are valid and reliable with a Cronbach's Alpha value of 0.847, and meet the classical assumption test so that the data is worthy of further analysis. The results of the hypothesis test indicate that product quality and service quality simultaneously have a significant effect on customer satisfaction with a significance value of 0.000 (<0.05). However, partially, only product quality has a significant effect on customer satisfaction, while service quality has no significant effect. The Adjusted R Square value of 0.430 indicates that the independent variable is able to explain 43% of the variation in customer satisfaction, while the rest is influenced by other factors outside the study. This finding indicates that product quality is a dominant factor in shaping e-commerce customer satisfaction compared to service quality. The implications of this research emphasize the importance of improving product quality and more adaptive service strategies to build sustainable customer satisfaction and strengthen loyalty in the increasingly competitive digital business environment.